Nativist and Islamist Radicalism Anger and Anxiety - Kaya, Ayhan; Benevento, Ayşenur; KOCA, Metin (Routledge Research in Race and Ethnicity, 2023)
This book analyses the factors and processes behind radicalisation of both native and self-identified Muslim youths. It argues that European youth responds differently to the challenges posed by contemporary flows of globalisation such as deindustrialisation, socio-economic, political, spatial, and psychological forms of deprivation, humiliation, and structural exclusion. The book revisits social, economic, political, and psychological drivers of radicalisation and challenges contemporary uses of the term "radicalism". It argues that neoliberal forms of governance are often responsible for associating radicalism with extremism, terrorism, fundamentalism, and violence. It will appeal to students and scholars of migration, minority studies, nationalisms, European studies, sociology, political science, and psychology.